Dampak Penggunaan Gadget terhadap Pembentukan Karakter Islami Gen Z - Ari Fajar Isbakhi; Yuli Widiyono; Hermawan Hermawan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In essence, technology has become an inseparable part of children's lives today. However, inappropriate use of technology can impact their development. The technology that exists today has a big influence on the progress of a nation and for this reason the role of parents and educators must be to be able to encourage and provide control and supervision to children so that they do not become addicted to technology. because technology can expand knowledge through the internet and digital devices, increase creativity to be creative in developing skills and can facilitate learning. However, current technology can also have negative impacts, such as children becoming dependent and spending time in front of screens, social interactions and even children having more fun in front of the screen than playing in the surrounding environment. In today's sophisticated era, being free from gadgets is difficult. Because gadgets are a major need for children and parents, because they can be used to communicate and carry out other needs. The aim of this research is to describe or describe in full the impact of gadget use on the social behavior of young children. The method used in this research is a qualitative method that will allow us to explore and analyze more complex problems, understand the perspectives of various stakeholders, and gain a deeper understanding of the context of the influence of devices on a child. The research hopes that the results obtained can be used as a benchmark for parents and teachers in controlling children's use of technology.